Interaksionisme Simbolik Peran "Ayah" pada Guru Laki-laki Pendidikan Anak Usia Dini di TK Muslimat NU I Nawakartika Ngawi - Intan Febriati Suyatno Putri (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the “father” role of male teachers in Early Childhood Education through the analysis of George Herbert Mead’s Symbolic Interactionism theory, particularly the concepts of Mind, Society, and Self. Male teachers interpret the “father” role through their interactions within the school environment. The purpose of this study is to understand the process through which male teachers construct the meaning of the father role using the perspective of symbolic interactionism. This research employs a case study method with a qualitative descriptive approach. Informants were selected using purposive sampling. Data were collected through observation, interviews, and documentation. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing.The findings reveal that male teachers in Early Childhood Education, through the lens of symbolic interactionism, demonstrate the symbols of caregiving, mentoring, discipline, and masculinity within the concept of Mind. These symbols are subsequently interpreted by Society, represented by female teachers, the principal, and parents, as symbols of the father role. Within the concept of Self, male teachers perceive themselves as “fathers” in the school setting based on their interactions and experiences.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: Guru Laki-laki; Pendidikan Anak Usia Dini; Peran Ayah; Simbol Ayah; Peran Guru Laki-laki Pendidikan Anak Usia Dini; Peran Ayah Guru Laki-laki PAUD